The Presence of Medical Sciences Faculty Members on Academic Social Networks and Its Relationship with Citations to Their Articles - Sirous Panahi; Sahar Maleki; Leila Nemati Anaraki; Ferdos Saraipour (International Journal of Information Science and Management, 2024)
Academic Social Networks (ASNs) are significant in forming scientific interactions and increasing the visibility of researchers' scientific works. Considering the growing importance of ASNs, the current study aimed to investigate the presence of Lorestan University of Medical Sciences faculty members in ASNs and its relationship with citations in their articles. Scientometrics and survey methods were used in this study. The population comprised 291 faculty members at Lorestan University of Medical Sciences. A questionnaire and a data collection form were utilized to investigate the presence of faculty members on ResearchGate, Academia, and citation databases, including Web of Science and Scopus. Descriptive (mean, variance) and analytical statistics (chi-square, Pearson, and Independent Samples T-test at a significance level of 0.05) were used to analyze the data using SPSS software. Academics of the faculty of medicine were the most active members of ResearchGate. Associate professors had the highest RG score compared to other academic ranks. However, the highest frequency of membership belonged to assistant professors. Following other researchers' activities and sharing articles were mentioned as advantages of joining ASNs. Isolation, staying away from the real social environment, and lack of information security were also disadvantages of ASNs. There was a positive correlation between scores of altmetrics indicators in ASNs and scientometrics indicators in citation databases. Concerning a positive correlation between altmetrics and scientometrics indicators, ASNs increase the visibility of scientific works and hence increase their citation.